2009
DOI: 10.1111/j.1439-0272.1986.tb01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Multinucleated Spermatocytes and Spermatids in Human Seminiferous Tubules*

Abstract: Thd cytology of multinucleated spermatocytes and spermatid giant cells in the seminiferous tubules of men with oligozoospermia and of men older than 65 years has been investigated electron microscopically. Two different processes which are responsible for the origin of multinucleated germ cells have been analysed: 1. Defects of the intercellular bridges (IB): they move apart and thus allow the confluence of one clone's cells to symplasms. 2. The confluence of membranes: within one clone the membranes of neighb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 14 publications
4
29
0
Order By: Relevance
“…The multinucleate giant cells derive mainly from clumped spermatogenic cells that have lost their contact to Sertoli cells [27,28]. The number of testicular sperm heads, which is known as a clear index of testicular cytotoxicity, correlated well with histopathological findings.…”
Section: Discussionmentioning
confidence: 91%
“…The multinucleate giant cells derive mainly from clumped spermatogenic cells that have lost their contact to Sertoli cells [27,28]. The number of testicular sperm heads, which is known as a clear index of testicular cytotoxicity, correlated well with histopathological findings.…”
Section: Discussionmentioning
confidence: 91%
“…5; left panels; [ +/+ ]). Moreover, we found multinucleated giant cells [58] in tubules of single Tas1r1 null mutant animals (Fig. 5; lower right panel; [ −/− ], arrow).…”
Section: Resultsmentioning
confidence: 97%
“…Giant cells arise from spermatacytes that abort meiosis and appear as a syncitium. Appearance of such giant cells is linked to defective spermatogenesis in genetically altered mice and in human pathologies linked to infertility 16, 17 . These observations suggested that ELMO1 is required for normal homeostasis of the seminiferous epithelium in mice.…”
mentioning
confidence: 99%